(untitled) (Eurasian Research Bulletin, 2022)
The purpose of the article is how to present grammatical information so that they do not become the leading aspect of learning a non-native language, but fully contribute to the formation and strengthening of communicative competencies. Naturally, the question of how to organize the work on the development of grammatical regularity in a school lesson of the Russian language cannot be separated from other aspects of comprehensive education: lexico-semantic, orthoepic, spelling work, from the work on the formation of communicative skills and abilities in all types of speech activity.